Azathioprine-Induced Acute Submandibular Sialadenitis in a Crohn's Disease Patient - Alves da Silva, Joana Inês (2020)
Introduction: Azathioprine (AZA) is a widely used immunosuppressive drug in inflammatory bowel disease (IBD). The occurrence of adverse effects (AEs) is a major downside in the use of this drug, leading to treatment withdrawal in a variable proportion of patients. Case presentation: We report the case of a Crohn's disease patient who developed sialadenitis as an AE to AZA. Discussion and conclusion: To our knowledge this AE has been reported only once in the literature. Sialadenitis is a common disorder and refers to inflammation of a salivary gland. It has many causes, such as bacterial and viral infections, ductal obstruction, and drugs. There are several AEs related to this drug, categorized as dose-dependent and dose-independent. Their knowledge is essential for therapeutic management in IBD, which is already challenging, requiring an individualized approach.